Nutrition before, during and after critical illness. Issue 4 (5th August 2022) - Ridley, Emma J.; Lambell, Kate
Abstract : Purpose of review: This review describes considerations preintensive care unit (ICU), within ICU and in the post-ICU period regarding nutrition management and the current state of the literature base informing clinical care. Recent findings: Within ICU, studies have focussed on the first 5–7 days of illness in mechanically ventilated patients who are heterogeneous and with minimal consideration to premorbid nutrition state. Many evidence gaps in the period within ICU remain, with the major ones being the amount of protein to provide and the impact of longer-term nutrition interventions. Personalised nutrition and nutrition in the post-ICU period are becoming key areas of focus. Summary: Nutrition for the critically ill patient should not be viewed in isolated time periods; what happens before, during and after ICU is likely important to the overall recovery trajectory. It is critical that the impact of nutrition on clinical and functional outcomes across hospitalisation is investigated in specific groups and using interventions in ways that are biologically plausible to impact. Areas that show promise for the future of critical care nutrition include interventions delivered for a longer duration and inclusion of oral nutrition support, individualised nutrition regimes, and use of emerging bedside body composition techniques to identify patients at nutritional risk.